2019
DOI: 10.1093/jas/skz393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrient Restriction During Midgestation to Late Gestation on Maternal and Fetal Postruminal Carbohydrase Activities in Sheep

Abstract: To examine the effects of nutrient restriction during midgestation to late gestation on maternal and fetal digestive enzyme activities, 41 singleton ewes (48.3 ± 0.6 kg of BW) were randomly assigned to dietary treatments: 100% (control; CON; n = 20) or 60% of nutrient requirements (restricted; RES; n = 21) from day 50 until day 90 (midgestation). At day 90, 14 ewes (CON, n = 7; RES, n = 7) were euthanized. The remaining ewes were subjected to treatments of nutrient restriction or remained on a control diet fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 77 publications
2
15
1
Order By: Relevance
“…Additionally, dietary fructose supplementation can induce sucrase activity in patients with congenital SI deficiency (Greene et al, 1972). However, several authors have failed to detect sucrase activity in the small intestine of cattle (Dollar and Porter, 1957;Huber et al, 1961;Siddons, 1968;Trotta et al, 2020a) and sheep (Walker, 1959;Shirazi-Beechey et al, 1989;Trotta et al, 2020b). Moreover, abomasal infusion of sucrose does not induce sucrase activity in lambs (Swanson and Harmon, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dietary fructose supplementation can induce sucrase activity in patients with congenital SI deficiency (Greene et al, 1972). However, several authors have failed to detect sucrase activity in the small intestine of cattle (Dollar and Porter, 1957;Huber et al, 1961;Siddons, 1968;Trotta et al, 2020a) and sheep (Walker, 1959;Shirazi-Beechey et al, 1989;Trotta et al, 2020b). Moreover, abomasal infusion of sucrose does not induce sucrase activity in lambs (Swanson and Harmon, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when fetal small intestinal maltase concentration was found to be decreased with maternal dietary intake restriction, fetal BW and small intestinal mass were also decreased (13.8% and 21.2%, respectively) [7,49]. Whereas when Trotta et al [38] found no differences in fetal small intestinal carbohydrase activities, fetal BW and small intestinal mass also did not differ compared to fetuses from ewes fed to meet NRC [50] recommendations. The fetal small intestine is relatively short in length compared to their maternal counterpart and therefore, differences in fetal intestinal sampling sites could be a potential explanation for variation in carbohydrase activities.…”
Section: Maternal Diet Influences On Small Intestinal Carbohydrase Acmentioning
confidence: 99%
“…Furthermore, fetal pancreatic α-amylase per gram of protein was not influenced when cows were restricted during either early or early-to-mid-gestation. In sheep, maternal dietary restriction during mid-, late-, or mid-to-late-gestation did not influence fetal pancreatic α-amylase activity [ 37 , 38 ]. Therefore, there could be species-specific responses to maternal nutrient restriction when comparing cattle and sheep.…”
Section: Influence Of Prenatal Nutrition On Fetal Carbohydrase Actmentioning
confidence: 99%
See 2 more Smart Citations